A method for preparing a negative electrode of an alkaline zinc-manganese battery

CN122224753BActive Publication Date: 2026-10-27FUJIAN NANPING NANFU BATTERY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610363739.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-24
Publication Date
2026-10-27
Estimated Expiration
2046-03-24

AI Technical Summary

Technical Problem

然而,超细锌粉虽然能提高放电性能,但难以兼顾电池的存储性能

Benefits of technology

[0012]由此,本发明从提升反应活性、保障体系均一、抑制自腐蚀析氢副反应三个维度相互支撑、精准适配,既针对性解决传统碱性锌锰电池的核心问题,又实现各技术手段的效果叠加,让电池在高功率大电流放电场景下的综合性能得到显著提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a preparation method of a negative electrode of an alkaline zinc-manganese battery, which adopts a three-in-one synergic design of high specific surface area zinc powder, negative electrode mixing process optimization and precise inhibitor addition, and through reasonable collocation of zinc powders with different particle sizes, the total surface area of the zinc powder is maximized, the reaction activity of the zinc powder is greatly improved, and the hydrogen evolution tendency is also as low as possible; in the negative electrode mixing process, the mixture of the zinc powder and the inhibitor is ball milled in an inert gas environment, a large number of defect sites are generated on the surface of the zinc powder through mechanical force, the delamination and sedimentation problem caused by the high specific surface area zinc powder is effectively relieved, the uniform distribution of the high specific surface area zinc powder in the negative electrode is ensured, and the uniform negative electrode reaction is ensured; the inhibitor keeps the uniform system constructed by the optimized stirring process stable, ensures that the uniform distribution state of the zinc powder is maintained throughout the whole battery discharging process, and enables the large-current discharging performance of the high-activity zinc powder to be continuously exerted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to battery processing technology, and more particularly to a method for preparing an alkaline zinc-manganese battery negative electrode. Background Technology

[0002] Alkaline batteries, as high-capacity disposable batteries, are widely used in portable electronic devices, lighting equipment, and emergency power supply. With societal development, people's performance requirements for batteries are constantly increasing, especially in terms of high-current discharge performance. While traditional alkaline zinc-manganese batteries possess good electrochemical performance, they have several shortcomings under high-power, high-current discharge conditions, mainly manifested in low zinc powder capacity utilization and decreased discharge performance.

[0003] To address these issues, researchers have explored various methods, such as using ultrafine zinc powder as the negative electrode material. However, while ultrafine zinc powder can improve discharge performance, it is difficult to simultaneously improve battery storage performance. Furthermore, existing technologies suffer from uneven distribution of the negative electrode active material with the electrolyte and other additives, leading to stratification and sedimentation. This affects the negative electrode reaction, thereby reducing the discharge performance of alkaline batteries and the consistency of discharge performance among alkaline batteries in the same batch. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing an alkaline zinc-manganese battery negative electrode.

[0005] The technical solution to achieve the objective of this invention is: a method for preparing an alkaline zinc-manganese battery negative electrode, wherein the alkaline zinc-manganese battery negative electrode is prepared using raw materials in the following weight ratio, with each component expressed in parts by weight: 60-80 parts zinc powder Electrolyte 18-38 parts, 0.8 to 1.2 parts of adhesive, Corrosion inhibitor 0.8–1.2 parts; The zinc powder has a specific surface area of ​​60-70 m². 2 / g; the electrolyte is 25% KOH by mass; the binder is potassium polyacrylate and / or sodium carboxymethyl cellulose; the corrosion inhibitor is any one or a combination of polyethylene glycol, triethanolamine and diethanolamine.

[0006] The method for preparing the alkaline zinc-manganese battery negative electrode of the present invention further includes the following steps: (1) The zinc powder and the corrosion inhibitor are mixed by ball milling in an inert gas (argon) environment, with a ball-to-material ratio of 10:1 to 15:1, a ball milling time of 2 to 4 hours, and a ball milling speed of 300 to 500 rpm to obtain a mixture; (2) Add the binder to the mixture obtained in step (1), stir evenly, stir at a speed of 100-150 rpm, and stir for 10-30 min; during the stirring process, slowly add the electrolyte, controlling the addition rate to 1-2 mL / s; (3) Continue stirring for 10 to 20 minutes to obtain a uniformly mixed negative electrode slurry.

[0007] Furthermore, the composition of the zinc powder includes any one of the following four cases, with each component expressed in parts by weight: Scenario 1: 0-10% of zinc powder has a particle size smaller than 40 mesh. Zinc powder with a particle size between 40 and 60 mesh, comprising 10-20%. Zinc powder with a particle size between 60 and 100 mesh, comprising 10-20%. Zinc powder with a particle size between 100 and 150 mesh, comprising 10-20%. 35% zinc powder with a particle size between 150 and 200 mesh. 5% zinc powder with a particle size between 200 and 325 mesh 0-5% of zinc powder has a particle size finer than 325 mesh; Scenario 2: 0-10% of zinc powder has a particle size smaller than 40 mesh. Zinc powder with a particle size between 40 and 60 mesh, comprising 10-20%. Zinc powder with a particle size between 60 and 100 mesh, comprising 10-20%. 30% zinc powder with a particle size between 100 and 150 mesh Zinc powder with a particle size between 150 and 200 mesh accounts for 40%. 2.5% zinc powder with a particle size between 200 and 325 mesh. 0-5% of zinc powder has a particle size finer than 325 mesh; Scenario 3: 0-10% of zinc powder has a particle size smaller than 40 mesh. Zinc powder with a particle size between 40 and 60 mesh, comprising 10-20%. Zinc powder with a particle size between 60 and 100 mesh, comprising 10-20%. Zinc powder with a particle size between 100 and 150 mesh, comprising 10-20%. Zinc powder with a particle size between 150 and 200 mesh accounts for 45%. 0% zinc powder with a particle size between 200 and 325 mesh 0-5% of zinc powder has a particle size finer than 325 mesh; Scenario 4: 0-10% of zinc powder has a particle size smaller than 40 mesh. Zinc powder with a particle size between 40 and 60 mesh, comprising 10-20%. Zinc powder with a particle size between 60 and 100 mesh, comprising 10-20%. Zinc powder with a particle size between 100 and 150 mesh accounts for 40%. 35% zinc powder with a particle size between 150 and 200 mesh. 0% zinc powder with a particle size between 200 and 325 mesh 0-5% of zinc powder has a particle size finer than 325 mesh.

[0008] Larger and finer particle sizes result in a larger specific surface area, higher reactivity, and a greater probability of battery leakage due to self-corrosion and hydrogen evolution. This invention, through a reasonable particle size distribution, maximizes the overall specific surface area of ​​the zinc powder while minimizing the proportion of ultrafine zinc powder finer than 325 mesh (ultra-high reactivity, ultra-high self-corrosion hydrogen evolution rate). This allows for maximizing reactivity while controlling the self-corrosion hydrogen evolution rate to prevent it from becoming excessively high.

[0009] Those skilled in the art know that high specific surface area zinc powder can fundamentally improve the reactivity of zinc powder and solve the problem of declining high-power, high-current discharge performance of traditional batteries. However, high specific surface area zinc powder itself will generate two major problems: its high specific surface area makes it more likely to separate and settle with electrolytes, binders, corrosion inhibitors and other components; and its high reactivity exacerbates its tendency to self-corrode and evolve hydrogen. If these two problems are not addressed in a targeted manner, the high reactivity of zinc powder cannot be effectively converted into the actual discharge performance of the battery, and the risk of battery leakage will be greatly increased.

[0010] To overcome this deficiency, this invention creatively proposes a synergistic design integrating the selection of high specific surface area zinc powder, optimization of the negative electrode mixing process, and precise addition of corrosion inhibitors. Specifically, by rationally combining zinc powders of different particle sizes, the total surface area of ​​the zinc powder is maximized, thereby improving its reactivity while minimizing hydrogen evolution tendency. Regarding the negative electrode mixing process, the mixture of zinc powder and corrosion inhibitor is first ball-milled in an inert gas environment. Mechanical force generates numerous defect sites on the zinc powder surface, increasing its surface energy, enhancing the adhesion of the corrosion inhibitor, and improving its compatibility with the electrolyte and binder. This effectively alleviates the stratification and sedimentation problem caused by high specific surface area zinc powder, ensuring uniform distribution of the high specific surface area zinc powder in the negative electrode and guaranteeing uniform negative electrode reaction. This effect not only allows all active sites of the highly active zinc powder to participate in the electrochemical reaction simultaneously, giving full play to its high-current discharge advantage, but also allows a small amount of corrosion inhibitor to achieve precise and uniform action on the evenly distributed zinc powder surface. This avoids the local enrichment / depletion of the corrosion inhibitor caused by zinc powder sedimentation, which leads to local failure or excess of the corrosion inhibitor. It ensures that the inhibitor's effect on suppressing hydrogen evolution from self-corrosion of high specific surface area zinc powder covers the entire negative electrode system.

[0011] On the other hand, this invention utilizes a corrosion inhibitor to address the problem of hydrogen evolution caused by the self-corrosion of high-specific-surface-area zinc powder, preventing hydrogen evolution from causing battery leakage. Simultaneously, effectively inhibiting hydrogen evolution fundamentally prevents hydrogen bubbles from damaging the overall structure of the negative electrode slurry, avoiding secondary sedimentation and agglomeration of zinc powder due to bubble impact. The corrosion inhibitor maintains the stability of the homogeneous system constructed by the optimized stirring process, ensuring that the uniform distribution of zinc powder persists throughout the entire battery discharge process, allowing the high-current discharge performance of the highly active zinc powder to be continuously maintained. The dosage of the slow-release agent is limited to 0.8–1.2 parts; too much will reduce the reactivity of the zinc powder and decrease the battery discharge performance; too little will not achieve the slow-release effect.

[0012] Therefore, this invention supports and precisely adapts itself to three dimensions: improving reaction activity, ensuring system uniformity, and suppressing self-corrosion hydrogen evolution side reactions. It not only specifically solves the core problems of traditional alkaline zinc-manganese batteries, but also achieves the superposition of the effects of various technical means, so that the overall performance of the battery is significantly improved in high-power, high-current discharge scenarios. Detailed Implementation

[0013] The preferred embodiments of the present invention will be described in detail below. Example 1

[0014] A method for preparing an alkaline zinc-manganese battery negative electrode, wherein the alkaline zinc-manganese battery negative electrode is prepared using raw materials in the following weight ratio, each component being in parts by weight: 70 parts zinc powder 28 parts of electrolyte, 1 part adhesive 1 part corrosion inhibitor, The zinc powder comprises the following components in parts by weight:

[0015] The zinc powder has a specific surface area of ​​70 m². 2 / g.

[0016] The method for preparing the alkaline zinc-manganese battery negative electrode further includes the following steps: (1) The zinc powder and the corrosion inhibitor were mixed by ball milling in an inert gas (argon) environment, with a ball-to-material ratio of 10:1, a ball milling time of 3 hours, and a ball milling speed of 400 rpm to obtain a mixture; (2) Add the binder to the mixture obtained in step (1), stir evenly at a stirring speed of 125 rpm for 20 min; slowly add the electrolyte during stirring, controlling the addition rate to 1.5 mL / s; (3) Continue stirring for 15 minutes to obtain a uniformly mixed negative electrode slurry.

[0017] Examples 2-5 Examples 2-5 use the same raw materials as Example 1 except for zinc powder, the difference being the particle size distribution and specific surface area of ​​the zinc powder, the weight fraction of the raw materials, and the process parameters. The zinc powder particle size distribution, specific surface area, composition, and process parameters of the alkaline zinc-manganese battery anodes of Examples 1-5 of this invention are shown in Table 1.

[0018] Comparative Example 1 Comparative Example 1 used the same raw materials as Example 1, except that no corrosion inhibitor was added. The particle size distribution, specific surface area, specific composition, and process parameters of the zinc powder in Comparative Example 2 are shown in Table 1.

[0019] Comparative Example 2 Comparative Example 2 used the same raw materials as Example 1 except for the zinc powder. The difference was that the zinc powder in Comparative Example 2 was zinc powder with normal specific surface area, and no corrosion inhibitor was added. The particle size distribution, specific surface area, specific composition, and process parameters of the zinc powder in Comparative Example 2 are shown in Table 1.

[0020] Table 1

[0021] The alkaline zinc-manganese battery negative electrodes obtained in Examples 1-5 and Comparative Examples 1 and 2 were used to assemble LR6 model batteries, and discharge tests were conducted. The test results are shown in Table 2. Table 2

[0022] As shown in Table 2, Comparative Example 1, which uses only high-specific-surface-area zinc powder without adding corrosion inhibitors and employs a conventional mixing method, exhibits discharge performance not significantly different from Examples 1-5, but suffers from severe leakage problems. Comparative Example 2, which uses only conventional-specific-surface-area zinc powder, does not have leakage problems, but its battery performance is lower than that of Examples 1-5. The alkaline battery negative electrode of Examples 1-5 of this invention improves the specific surface area of ​​zinc powder by rationally combining zinc powder with different particle sizes, thereby enhancing discharge performance. Simultaneously, through optimized negative electrode mixing process and precise addition of corrosion inhibitors, the corrosion inhibitors are uniformly and effectively applied to the zinc powder. Compared to simply using ultrafine high-specific-surface-area zinc powder, it maintains high battery storage and leakage prevention performance, achieving a balance between high-current performance and storage performance, thus meeting the ever-increasing demand for high-current discharge.

[0023] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent process transformations made using the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A method for preparing an alkaline zinc-manganese battery negative electrode, characterized in that: The negative electrode of the alkaline zinc-manganese battery is made from the following raw materials in the indicated weight ratios. Prepare the following: Each component is listed in parts by weight: 60-80 parts zinc powder, Electrolyte 18-38 parts, 0.8–1.2 parts of adhesive, Corrosion inhibitor 0.8–1.2 parts; The zinc powder has a specific surface area of ​​60-70 m². 2 / g; The zinc powder composition includes any one of the following four cases, with each component expressed in parts by weight: Scenario 1: 0-10% of zinc powder has a particle size smaller than 40 mesh. Zinc powder with a particle size between 40 and 60 mesh, comprising 10-20%. Zinc powder with a particle size between 60 and 100 mesh, comprising 10-20%. Zinc powder with a particle size between 100 and 150 mesh, comprising 10-20%. 35% zinc powder with a particle size between 150 and 200 mesh. 5% zinc powder with a particle size between 200 and 325 mesh 0-5% of zinc powder has a particle size finer than 325 mesh; Scenario 2: 0-10% of zinc powder has a particle size smaller than 40 mesh. Zinc powder with a particle size between 40 and 60 mesh, comprising 10-20%. Zinc powder with a particle size between 60 and 100 mesh, comprising 10-20%. 30% zinc powder with a particle size between 100 and 150 mesh Zinc powder with a particle size between 150 and 200 mesh accounts for 40%. 2.5% zinc powder with a particle size between 200 and 325 mesh. 0-5% of zinc powder has a particle size finer than 325 mesh; Scenario 3: 0-10% of zinc powder has a particle size smaller than 40 mesh. Zinc powder with a particle size between 40 and 60 mesh, comprising 10-20%. Zinc powder with a particle size between 60 and 100 mesh, comprising 10-20%. Zinc powder with a particle size between 100 and 150 mesh, comprising 10-20%. Zinc powder with a particle size between 150 and 200 mesh accounts for 45%. 0% zinc powder with a particle size between 200 and 325 mesh 0-5% of zinc powder has a particle size finer than 325 mesh; Scenario 4: 0-10% of zinc powder has a particle size smaller than 40 mesh. Zinc powder with a particle size between 40 and 60 mesh, comprising 10-20%. Zinc powder with a particle size between 60 and 100 mesh, comprising 10-20%. Zinc powder with a particle size between 100 and 150 mesh accounts for 40%. 35% zinc powder with a particle size between 150 and 200 mesh. 0% zinc powder with a particle size between 200 and 325 mesh 0-5% of zinc powder has a particle size finer than 325 mesh; The electrolyte is KOH with a mass fraction of 25%; The adhesive is potassium polyacrylate and / or sodium carboxymethyl cellulose; The corrosion inhibitor is any one or a combination of polyethylene glycol, triethanolamine, and diethanolamine; The method for preparing the alkaline zinc-manganese battery negative electrode further includes the following steps: (1) The zinc powder and the corrosion inhibitor are mixed by ball milling in an inert gas environment, with a ball-to-material ratio of 10:1 to 15:1, a ball milling time of 2 to 4 hours, and a ball milling speed of 300 to 500 rpm to obtain a mixture; (2) Add the binder to the mixture obtained in step (1), stir evenly, stir at a speed of 100-150 rpm, and stir for 10-30 min; slowly add the electrolyte during stirring, and control the addition rate to 1-2 mL / s. (3) Continue stirring for 10 to 20 minutes to obtain a uniformly mixed negative electrode slurry.

Citation Information

Patent Citations

  • Alkaline zinc-manganese battery negative electrode material as well as preparation method and application thereof

    CN115663193A

  • High-power alkaline manganese battery negative electrode and application method thereof

    CN118073516A